If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3x-4)-8=x-6
We move all terms to the left:
2(3x-4)-8-(x-6)=0
We multiply parentheses
6x-(x-6)-8-8=0
We get rid of parentheses
6x-x+6-8-8=0
We add all the numbers together, and all the variables
5x-10=0
We move all terms containing x to the left, all other terms to the right
5x=10
x=10/5
x=2
| 29+5x=8x+11 | | 3(x+15)=4-2x | | 16x=8x(x+10) | | 10x-5(2x-7)+2=45 | | -48.8=6.1c | | x/8=10+x/16 | | 10(3–x)–4(6–8x)+1,5(4–10x)–26=0 | | 91/3=-195/7x | | nC(n-2)=10 | | 5x-(15x-7)=x-26 | | 3x(9x+5)=-66 | | 9.1/3=-19.5/7x | | 3(2x-1)+2(3x-2)=29 | | 2.4x-0.3x^2-2.1=0 | | (3x+2)/(x-4)=-5 | | 3x-1-(x+2)=1 | | 10x-(x-5)=14 | | 4.8=b-5.9 | | 37x+33=69+x | | 37x33=69+x | | 0.5(4x-8)=5x+2 | | s/7=-3.7 | | 3(x+1)=4x-8 | | 8(2x+1)=4(x-4) | | 2(x+4)=5(x+1) | | f+3/4=14 | | (1/2)(x+4)=8 | | 46x-2=100-5x | | 9.3x+65.14=-10.7x+64.02 | | 15x-5=7-10x | | y+65/9=10 | | 9.5x+50.82=-10.5x+50.12 |